2019
DOI: 10.1080/21691401.2019.1645155
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin-functionalized three-dimensional magnetic SBA-16 for treating breast cancer cells (MCF-7)

Abstract: The engineering of multifunctional therapeutics in an integrated single platform is demonstrated using three-dimensional . 10 wt% iron oxide nanoparticles (Fe) were loaded into the cage type of cubic pores through enforced adsorption technique. Fe/S-16 is then functionalized with amine-based silane (A), polyacrylic acid (P) and cisplatin (Cp). The physicochemical textural analysis showed the formation of nano metal oxide distributions at pore walls of S-16 with magnetization of 2.39 emu/g. S-16 based nanoformu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Slightly enhanced generation of complex DNA lesions in irradiated GNP(+) cells compared to GNP(−) cells can be explained considering recent studies, in which small nanoparticle amounts were detected in the cell nucleus by Transmission Electron Microscopy (TEM) [117][118][119][120] or Raman Spectroscopy [121]. This can theoretically happen either due to disruption of the nuclear envelope by ROS (generated by nanoparticles in the cytoplasm) or during mitosis, when the envelope is disintegrated [122].…”
Section: Discussionmentioning
confidence: 99%
“…Slightly enhanced generation of complex DNA lesions in irradiated GNP(+) cells compared to GNP(−) cells can be explained considering recent studies, in which small nanoparticle amounts were detected in the cell nucleus by Transmission Electron Microscopy (TEM) [117][118][119][120] or Raman Spectroscopy [121]. This can theoretically happen either due to disruption of the nuclear envelope by ROS (generated by nanoparticles in the cytoplasm) or during mitosis, when the envelope is disintegrated [122].…”
Section: Discussionmentioning
confidence: 99%
“…Herein, the IC50 concentrations were 7 and 15 µl for the cancer and normal cell lines. The mechanism of lower toxicity against normal cell lines compared to cancer cell lines had been approved by most studies [61,[92][93][94]. Some groups reported that the corresponding difference has been related to the higher sensitivity of cancer cells to nanoparticles [61] due to their higher metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…The activation of MNPs using an alternating magnetic field has been intensively explored recently for targeted therapeutic heating of tumors. Superparamagnetic and ferromagnetic particles, with different coatings and functionalities have been shown to be effective in tumor therapy [10,94]. There are several routes of MNPs administration in magnetic hyperthermia, the most popular being the intra-tumoral and intravenous applications.…”
Section: Hyperthermiamentioning
confidence: 99%